PENGGUNAAN AI DALAM PRESENTASI PASTORAL MAHASISWA STIPAS SANTO SIRILUS RUTENG: IMPLIKASI TERHADAP KEMANDIRIAN DAN BERPIKIR KRITIS - Kurniawan, Maria A.; Manus, Maria D.J.; Marsa, Fransiska A.; Palmu, Kristina N.; Jani, Maria Afrila; Bandur, Hironimus; Harjon, Losianus; Molan Jawang, Petrus Paulus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This stady aims to analyze the use of AI in pastoral presentations among students of STIPAS Santo Sirilus Ruteng abd its implications for learning independence and critical thinking skills. The study employed a qualitative approach with a descriptive research design. The research subjects were studendts who used AI, particularly Chat GPT, in pastoral presentation activities. Data were collected through observation, in-depth interviewa, and documentation, while data analysis used an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that the use of AI helped students accsess information quickly, organize presentations materials, and improve learning effectiveness. However, excessive use tended to create intellectual dependency, reduce learning independence, and weaken students’ critical thinking abilities in analyzing and reflecting on pastoral issue deeply. Students who used AI proportionally were still able to maintain reflective and analytical abilities in the learning process. Therefore, the use of AI in pastoral education needs to be directed ethically, critically, and responsibly through appropriate pedagogical guidance.